1997
DOI: 10.1152/ajplung.1997.272.6.l1133
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide attenuates hydrogen peroxide-mediated injury to porcine pulmonary artery endothelial cells

Abstract: To examine the role of nitric oxide (.NO) in vascular endothelial cell injury, cultured porcine pulmonary artery endothelial cells (PAEC) were treated with H2O2 (100-500 microM) for 30 min in the presence or absence of the .NO donors (+/-)S-nitroso-N-acetylpenicillamine (SNAP) or diethylamine nitric oxide (DEANO). H2O2 caused dose-dependent PAEC cytotoxicity detected 2 h after H2O2 treatment as the release of lactate dehydrogenase. SNAP (100 microM) and DEANO (100 microM) attenuated H2O2-induced cytotoxicity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 0 publications
4
20
0
1
Order By: Relevance
“…Therefore, we determined whether CF exosome release is altered in various injuring settings, including inflammation, hypoxia, and oxidative stress in cultured PAEC. To mimic these settings, LPS [17], hypoxic culture conditions [11], and H 2 O 2 [18] were used. We measured the total amount of proteins (concentrations) and protein expression levels of exosome markers CD63 in total exosomes released from the same number of PAEC after the treatment, as noted above.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we determined whether CF exosome release is altered in various injuring settings, including inflammation, hypoxia, and oxidative stress in cultured PAEC. To mimic these settings, LPS [17], hypoxic culture conditions [11], and H 2 O 2 [18] were used. We measured the total amount of proteins (concentrations) and protein expression levels of exosome markers CD63 in total exosomes released from the same number of PAEC after the treatment, as noted above.…”
Section: Resultsmentioning
confidence: 99%
“…Refs. 20, 21, 45, and 61), others have suggested that NO protects against reactive oxygen species (62,63). A plausible explanation for this apparent paradox is that both NO and H 2 O 2 can show very different effects depending on their concentrations.…”
mentioning
confidence: 99%
“…O 2-and NO radicals, although they cannot react directly with GSH, can oxidize GSH after undergoing intracellular redox reactions NO can react with O 2-by radical-radical interaction forming peroxynitrite (ONOO -), thus clearing and scavenging O 2-in a diffusion limited rate. [61][62][63] ONOO -is a strong oxidizing agent, a reactive nitrogen species which oxidizes GSH rapidly to GSSG and depletes intracellular store of GSH. Similar results for glutathione system have been previously reported as decrease in GSH levels of maternal and fetal liver at 3 h, 6 h and 16 h after LPS injection to pregnant mice was observed.…”
Section: Discussionmentioning
confidence: 99%